2010
DOI: 10.1016/j.atherosclerosis.2009.09.070
|View full text |Cite
|
Sign up to set email alerts
|

Association of telomere length with type 2 diabetes, oxidative stress and UCP2 gene variation

Abstract: ObjectiveHigh oxidative stress potentially leads to accelerated telomere shortening and consequent premature cell senescence, implicated in type 2 diabetes (T2D) development. Therefore, we studied the association of leukocyte telomere length (LTL) with the presence of T2D, as well as the effect on the patients’ LTL of plasma oxidative stress and of variation in UCP2, a gene involved in the mitochondrial production of reactive oxygen species.MethodsMean LTL was determined in 569 Caucasian, 103 South Asian and 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
202
3
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(222 citation statements)
references
References 48 publications
10
202
3
7
Order By: Relevance
“…Consistently, mice expressing a variant of the mitochondrial uncoupling protein 2 that increases ROS production by ETC, and therefore, oxidative stress shows short telomeres (Salpea et al ., 2010). Moreover, it has been shown that treating mouse embryos with chemicals able to induce mitochondrial dysfunction and ROS accumulation, led to telomere loss and chromosomal instability, which was prevented by a concomitant treatment with N ‐acetylcysteine, a compound that improves ROS scavenging (Liu et al ., 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, mice expressing a variant of the mitochondrial uncoupling protein 2 that increases ROS production by ETC, and therefore, oxidative stress shows short telomeres (Salpea et al ., 2010). Moreover, it has been shown that treating mouse embryos with chemicals able to induce mitochondrial dysfunction and ROS accumulation, led to telomere loss and chromosomal instability, which was prevented by a concomitant treatment with N ‐acetylcysteine, a compound that improves ROS scavenging (Liu et al ., 2002).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have addressed this question, examining associations of leucocyte TL (LTL), which largely reflects TL in other somatic cells [4], with indices of insulin resistance or with type 2 diabetes mellitus. The majority [5][6][7][8][9][10][11][12] but not all [13,14] of these studies found that LTL (or TL in subsets of leukocytes) was inversely associated with insulin resistance or that LTL was shorter in patients with type 2 diabetes mellitus than in individuals without the disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations that decrease telomerase and cause short telomeres in humans lead to a spectrum of premature-onset diseases and conditions collectively termed "telomere syndromes," which share many features of the common diseases of aging in the human population (Armanios and Blackburn 2012). Multiple independent studies have found impaired human telomeric DNA length maintenance to be associated with a wide range of diseases and for several age-related diseases to predict future risks and outcomes including mortality (Von Zglinicki et al 2000;Samani et al 2001;Cawthon et al 2003;Panossian et al 2003;Valdes et al 2005;Bischoff et al 2006;Harris et al 2006;MartinRuiz et al 2006;Bakaysa et al 2007;Brouilette et al 2007;Fitzpatrick et al 2007Fitzpatrick et al , 2011Aubert and Lansdorp 2008;Farzaneh-Far et al 2008;Kimura et al 2008;Epel et al 2009;Njajou et al 2009;Astrup et al 2010;Codd et al 2010Codd et al , 2013Salpea et al 2010;Willeit et al 2010a,b;Zee et al 2010;Strandberg et al 2011;Wentzensen et al 2011;Yaffe et al 2011;Honig et al 2012;Lee et al 2012;Weischer et al 2012;Bojesen 2013;Muezzinler et al 2013;Gardner et al 2014;Haycock et al 2014;Walsh et al 2014).…”
mentioning
confidence: 99%